Analisis Pertumbuhan Ekonomi dan Penyerapan Tenaga Kerja di Provinsi Riau - Hidayat, Muhammad; Nurlela, Nurlela (Akuntansi & Ekonomika, 2018)
This study aims to determine the effect of wages, education, and economic growth on employment and knowing the effect of wages, unemployment, investment, and labor on economic growth in Riau Province. The analysis tool used is a regression of simultaneous equations - Two-Stage Least Square (TSLS). Based on the results of the study indicate that in the simultaneous equation I (Labor), Wages have a positive and significant influence, while education has a negative and significant influence, and economic growth is negatively and not significantly related to employment absorption; In simultaneous equation II (Economic Growth), Wages have a negative and not significant relationship, while unemployment and investment have a positive and insignificant effect, and for labor has a positive and significant relationship to economic growth.